PENGARUH PENGENDALIAN INTERN DAN PEMANFAATAN SISTEM INFORMASI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Kasus Pada Organisasi Perangkat Daerah di Kabupaten Batang) - Fangela Myas Sari (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2022)
This study aims to determine the effect of internal control, human resources in the field of accounting and the use of regional financial information systems on the quality of local government financial reports. Data was collected by distributing questionnaires 50 which did not return 11, which were distributed to staff/employees of the finance subdivision such as the expenditure treasurer, income and expenditure treasurer at the Regional Apparatus Organization in Batang Regency.The test results show that the Internal Control System has no significant effect on the quality of local government financial reports (Pvalue 0.277), and the use of regional financial information systems has a significant effect on the quality of local government financial reports (P value 0.003). The results of this study indicate that internal control has no effect, while the utilization of regional financial information systems has an effect on the quality of regional government financial reports. Keywords: Internal Control System, Utilization of Regional Financial Information Systems and Quality of Local Government Financial Reports